Implementasi Pembelajaran Menyenangkan dengan Model Teams Games Tournament (TGT) untuk Memudahkan Pembelajaran IPA Terhadap Peserta Didik - Eva Maghfiroh; Syamsul Arifin (Bidayatuna, 2021)
The current learning pattern is in principle a process to make understanding of a material easier to understand, through this process it is hoped that students can and easily understand each subject. Educators need to create a pleasant learning atmosphere so that students do not feel burdened in carrying out learning activities. By using the right media in the learning process it will be more interesting and fun and also help students more easily understand the material being taught. Implementing fun learning is needed in all lessons that are considered difficult for students to understand. The learning process with the game system used in the Teams Games Tournament learning is hoped that students receive material that is easier to understand, relax, and can also foster a sense of responsibility and togetherness in teaching and learning.